The Development of Islam in Sinjai Through ‎the to Panrita Kitta in the Seventeenth ‎Century - Wahyu,; Syukur, Syamzan (Al-Hikmah, 2025)
This study aims to describe and analyze the development of Islam through the role of To Panrita Kitta after Islam was accepted in the Sinjai region. This study is a historical study with a qualitative descriptive analysis method using a sociological and anthropological approach. The stages of the study consist of heuristics, source criticism, interpretation, and historiography. The results of the study indicate that after the acceptance of Islam in the 17th century, a number of figures or scholars in Sinjai, known as To Panrita Kitta, played an important role in developing Islamic teachings and its sharia. The role of To Panrita Kitta is not only limited to religious aspects, but also in shaping the cultural identity, moral values, and character of the Sinjai community. Through a historical approach and cultural studies, this study reveals the main contribution of To Panrita Kitta to the development of local civilization based on science, spirituality, and traditional wisdom. The presence of Islam in Sinjai is not only as a belief system, but also as a way of life that is implemented in the socio-cultural order of society. This creates a process of acculturation between local culture and Islamic values ​​that continues to develop to current days.